ABOUT A PROBLEM OF OPTIMAL CONTROL OF STEPWISE CHANGING LINEAR SYSTEMS WITH PHASE STATES RESTRICTIONS IN INTERMEDIATE MOMENTE - Barseghyan, V. R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2002)
Problem of optimal control of stepwise changing linear systems with phase restrictions in intermediate instants is investigated at a specific criterions of quality on the whole time interval and method of a solution is offered.